2012
DOI: 10.4149/gpb_2012_030
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged oxytocin treatment in rats affects intracellular signaling and induces myocardial protection against infarction

Abstract: Oxytocin is a hormone, which is released into the circulation in response to acute or chronic stress stimuli. One of the important targets of oxytocin is cardiovascular system. Present studies were aimed at testing the hypothesis that prolonged treatment with oxytocin (simulation of stress-induced rise in circulating oxytocin) activates intracellular signaling pathways playing a role in ischemia/reperfusion injury. Furthermore, we tested protective effects of oxytocin treatment in vivo against cardiac injury i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 31 publications
0
23
0
Order By: Relevance
“…Most of the up-to-date studies on the role of oxytocin in myocardial infarction were based on experimental methods involving an ischaemia-reperfusion model in vitro [19, 26, 27] or in vivo [16, 17]. In the study by Jankowski et al, myocardial infarction was evoked by chronic ligation of the left anterior descending coronary artery [17].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the up-to-date studies on the role of oxytocin in myocardial infarction were based on experimental methods involving an ischaemia-reperfusion model in vitro [19, 26, 27] or in vivo [16, 17]. In the study by Jankowski et al, myocardial infarction was evoked by chronic ligation of the left anterior descending coronary artery [17].…”
Section: Resultsmentioning
confidence: 99%
“…The authors of that study did not measure oxytocin mRNA expression and protein level at the same time; thus, it cannot be excluded that endogenous intracardiac OT could be partially responsible for the observed cardioprotective effects. In the other study, pretreatment with OT before ischaemia-reperfusion exposure resulted in the reduction of infarct size and activation of the prosurvival p38-MAPK and Akt-kinase pathways [26, 27]. In the in vitro model of ischaemia-reperfusion-induced myocardial damage, Ondrejcakova et al showed that exposure to OT prior to ischaemia resulted in the reduction of the infarct size due to the negative chronotropic effect [19].…”
Section: Resultsmentioning
confidence: 99%
“…This is particularly exciting given that other substances, such as exendin-4, typically fail to maintain body weight loss after 17 days [218]. Of obvious clinical significance are findings that indicate oxytocin reduces anxiety [219], blood pressure [220], the size of cardiac infarcts [221], and is not causally related to the development of a CTA [222] in rats. Moreover, CNS [13] administration of oxytocin fails to elicit a CTA at doses that suppress food intake and body weight in rodents [12, 14, 36].…”
Section: Oxytocin As a Potential Therapeutic Target?mentioning
confidence: 99%
“…Potential protection via SLP-dependent ANP/BNP expression is consistent with impaired I-R tolerance in mice lacking the natriuretic peptide receptor guanylyl cyclase-A [33]. Furthermore, cardioprotection with prolonged oxytocin is associated with ANP expression [34], and post-ischemic Nbbp correlates with I-R tolerance in a model of epoxyeicosatrienoic acid mediated protection [35]. Nonetheless, mechanistic involvement of the peptides in these and other protective responses remains to be established.…”
Section: Discussionmentioning
confidence: 93%